(untitled) (Research, Society and Development, 2020)
The aim of this text is to present the preliminary results of an ethnographic study entitled La contenzione del paziente psichiatrico: Un’indagine sociologica e giuridica, written by the researchers Mario Cardano, Alessandra Algostino, Marta Caredda, Luigi Gariglio and Cristina Pardini, based on the interview that the leading researcher provided to the Italian site Letture.org. The study had as starting point a set of questions which were included in the following leading question: What cultural and organizational aspects Diagnosis and Healing Psychiatric Services determine the use of mechanical restraint? It is important to think about the historical process of comprehension related to mental disorder and crisis, the way of care, the traditional coercive practices, as the mechanical restraint in Piedmont and Friuli Venezia Giulia regions, Italy, which reinforce similar models from other countries, like in Brazil.